2019
DOI: 10.1182/blood.2019000050
|View full text |Cite
|
Sign up to set email alerts
|

γ-Secretase inhibition increases efficacy of BCMA-specific chimeric antigen receptor T cells in multiple myeloma

Abstract: Despite notably high response rates to B-cell maturation antigen (BCMA) chimeric antigen receptor (CAR) T cells in multiple myeloma, few patients have a sustained, very good partial or complete response. This article presents a novel strategy to increase the efficacy of BCMA-directed CAR T-cell therapy and shows that γ-secretase inhibitors improve the efficacy of BCMA CAR T cells by increasing BCMA expression and reducing soluble BCMA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
200
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 240 publications
(223 citation statements)
references
References 65 publications
5
200
1
1
Order By: Relevance
“…Knocking down BCMA itself or its transcription factor POU2AF1 (16) both resulted in significant downregulation of cell surface BCMA expression, thus validating the screen ( Fig 1C). Furthermore, all of the subunits of the gamma secretase complex were among the top hits, and their knockdown resulted in a significant increase in cell surface BCMA ( Fig 1C), consistent with previous reports from other groups (6,9). Moreover, we identified several functional categories of genes regulating expression levels of BCMA including subunits of the Sec61 translocon complex, peroxisome biogenesis, proteasome subunits, and regulators of transcription ( Fig 1C).…”
Section: Genome-wide Crispr Screens To Identify Genes Controlling Celsupporting
confidence: 89%
“…Knocking down BCMA itself or its transcription factor POU2AF1 (16) both resulted in significant downregulation of cell surface BCMA expression, thus validating the screen ( Fig 1C). Furthermore, all of the subunits of the gamma secretase complex were among the top hits, and their knockdown resulted in a significant increase in cell surface BCMA ( Fig 1C), consistent with previous reports from other groups (6,9). Moreover, we identified several functional categories of genes regulating expression levels of BCMA including subunits of the Sec61 translocon complex, peroxisome biogenesis, proteasome subunits, and regulators of transcription ( Fig 1C).…”
Section: Genome-wide Crispr Screens To Identify Genes Controlling Celsupporting
confidence: 89%
“…As BCMA is actively cleaved away from myeloma cell surface by the gamma-secretase complex, study has shown that small-molecule gamma-secretase inhibitor was able to increase BCMA expression on myeloma cells, hence able to increase CAR T-cell efficacy [220]. Combining CAR-T cell therapy with immunomodulatory drug [221] or checkpoint inhibitor [222] are interesting options to be explored.…”
Section: Durability Of Response With Car-t Cell Therapiesmentioning
confidence: 99%
“…However, the variable density of BCMA on MM cells in different patients and the propensity of target escape after initial BCMA-targeting immunotherapy may compromise therapeutic efficacy. For example, BCMA on the cell surface can be cleaved by γ-secretase [77], and the resulting reduced cell surface level of BCMA and increased serum level of soluble BCMA could potentially limit the efficacy of BCMA-directed adoptive T-cell therapy by inhibiting CAR T-cell recognition of BCMA on myeloma cells [33,78,79]. Therefore, targeting other members in this ligand-receptor subgroup such as TACI, either alone or in combination with BCMA-targeting therapies, might achieve better clinical efficacy or improve the treatment outcome for MM patients.…”
Section: Targeting Taci In Immunotherapy Against MMmentioning
confidence: 99%